A collaborative and open solution for large‐scale online learning. Issue 6 (7th August 2018) - Zhou, Qingguo; Sun, Hongyu; Zhou, Rui; Sun, Geng; Shen, Jun; Li, Kuan‐Ching
Abstract: Collaborative Open Online Courses (COOC), designed as the enhanced variance of Massive Open Online Courses (MOOC), inherently combines the advantages of high‐quality online resources and face‐to‐face classroom teaching. It stimulates the collaboration and improvement of courses between educators and learners, by realizing the innovation for dynamic and real‐time education process, fostering professional skill acquisition and development as well. In this paper, we propose the novel concept and architectural design of COOC that provides the online course, courseware, and online experimental platform, built on top of third party's open source platforms. The preparation of courses is based on GitHub that facilitates multipoint‐to‐multipoint online courses and concurrent compilation of textbook based on GitBook, by providing open source textbooks and rapid updates as well as remote operations through online experimental platforms. The major differences between MOOC and COOC include decentralized platform and adoption of concepts through crowdsourcing, where instructors, professionals, and learners are able to set up and modify the courses independently and concurrently, empowering the course's construction based on the collaborative, open and shared textbooks, and online experimental platform. Users, including both teachers and learners, are also able to browse, download, and make use of courses in this platform. With embedded intellectual property and quality control mechanisms, such as Creative Commons (CC) licenses, COOC platform can generate and offer high‐quality courses and textbooks of emerging knowledge rapidly through consistent updates by professionals, students, and elites in related domains. The proposed design has been tested at trial Chinese universities and initial feedback from instructors and students are very positive. Insights on techniques and related information are provided, to best adapt to any vocational education level, subject matter, or courseware provider.